Metastatic Status and Dissection Effect of Regional/Extraregional Lymph Nodes in Japanese Patients with Squamous Cell Carcinoma of the Anal Canal: A Multicenter Retrospective Cohort Study - Takayuki Torigoe; Keiji Hirata; Kazutaka Yamada; Yoichi Ajioka; Kenichi Sugihara (Journal of the Anus, Rectum and Colon)
Objectives: Squamous cell carcinoma of the anal canal (SCCA) is a rare condition. Standard treatment includes chemoradiotherapy, with surgical treatment reserved for limited cases. In the future, the decrease in surgical frequency makes it more difficult to pathologically assess the depth of tumor invasion and lymph node status; therefore, those studies based on relatively recent surgical cases may offer valuable insights into diagnosing and treating SCCA. Methods: This multicenter, retrospective cohort study evaluated 435 patients with SCCA in Japan, of which 84 underwent surgical lymph node dissection. The correlation of regional/extraregional lymph node metastasis with T-primary tumor category/depth of tumor invasion, and the index of estimated benefit from lymph node dissection (IEBLD) was evaluated histopathologically. Results: Primary tumor progression was associated with metastasis and recurrence of the inguinal node and further inferior mesenteric trunk/root node metastasis, an extraregional lymph node. The IEBLD for the inferior mesenteric trunk/root node was 6.9, which was higher than 4.0 IEBLD of the lateral lymph nodes classified as the regional lymph nodes. Conclusions: The assessment of the primary tumor involvement can predict metastases of the inguinal node and inferior mesenteric trunk/root node and recurrence of the inguinal node. Although the UICC TNM Classification considered the inferior mesenteric trunk/root nodes as extraregional lymph nodes, actively targeting them with the treatment can improve the prognosis.